PENGARUH ESKTRAKULIKULER PRAMUKA TERHADAP KARAKTER SEMANGAT KEBANGSAAN PESERTA DIDIK DI SMA NEGERI 12 PEKANBAU - Sitorus, Debora Sari; Gimin, Gimin; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This Research event will be based on the spirit of nationality that has begun to wear off over time especially among students in SMA Negeri 12 pekanbaru. Formulation of the problem in this research is: "are there any extra-curricular activities influence influence Scout against the spirited character nationality students in SMA Negeri 12 Pekanbaru?". This research aims to know the influence of the Ekstrakulikuker Scout against the Spirited Character Nationality Students In SMA Negeri 12 Pekanbaru. This research was conducted at SMA Negeri 12 Pekanbaru in July and August 2018. This research is a descriptive quantitative research into the population in this research is the learners SMA Negeri 12 Pekabaru the following extracurricular activities Scouts amounted to 41 people. The sample in this study is taken based on the technique of saturated samples (total sampling), i.e. when the number of the subject is less than 100, more well taken all of his research is the research so that the population, thus the sample of this research is the entire learners SMA Negeri 12 Pekanbaru who follow Scouting extracurricular activities amounted to 41 people. Later data analysis using quantitative descriptive technique by using statistical tests. Based on the results of the study showed that there was no influence between extracurricular activities Scouts against character semagat nationality in SMA Negeri 12 Pekanbaru Fhitung < Ftabel, or 4.09, of which 3,977 < magnitude of contributions or donations notable alumni of the national spirit of the characters against the Scouts indicated by the magnitude of the R square or the coefficient of Determination (R2) 0.069. This means that extracurricular learning, Scouts contribute to 6.9% against the spirit of the nationality character of learners in SMA Negeri 12 Soweto. Thus the hypothesis that reads there is the influence of character against the spirit of the Scout extracurricular nationality in SMA Negeri 12 Pekanbaru, was rejected.Keywords: Esktrakulikuler Scout, Character The Spirit Of Nationality